Tourism-Income Inequality Nexus in Africa: Evidence from SADC countries (2023)
The tourism sector is one of the fastest-growing services sub-sectors worldwide and promises to unlock job opportunities and improve social inclusion outcomes in developing countries. We focused on the Southern African Development Community (SADC) region, which houses developing countries with high income inequality and constitutes attractive tourist centres in sub-Saharan Africa. We employed both the disaggregated and composite indicators of tourism development to investigate the tourism-income inequality nexus in the SADC region from 2010 to 2019. Utilizing the panel quantile regression approach, our overall results suggest that tourism development is inequality-worsening, and this is robust to both the composite tourism index and the individual tourism indicators (except in a few instances). While we established that net FDI inflows improve the inequality outcomes in the region, less corruption worsens inequality (except in a few cases). Accordingly, we offer relevant policy options for the governments of the SADC region.